IDENTIFICATION Aspergillus Sp ON MUNG BEANS AT ANDIR MARKET, BANDUNG CITY - Ni'matul Murtafi'ah; Suyarta Efrida Pakpahan; Muhammad Dihan (Jurnal Kesehatan Rajawali, 2022)
Mung bean is a carbohydrate food with a fairly high nutritional content, carbohydrate food has the composition needed by a microorganism, one of which is mushrooms. Mung bean is also a food ingredient that is often found in traditional markets such as Andir Market. The humid market environment and open storage areas make it easier for mung beansto be contaminated by fungi such asAspergillusSp. This study aims to determine the types of Aspergillus Sp which contaminates mung beanssold at Andir Market, Bandung City. The research method used is descriptive by using the total population. This research was conducted using the sowing method and observed macroscopically and microscopically. The results in this study are known to Aspergillus Sp with a percentage that isAspergillus fumigatus(40%). Aspergillus niger and Aspergillus terreus (20%) and there is 1 negative sample Aspergillus Sp. In this study it was concluded that there are types ofAspergillusSp in mung beanssold at the Andir Market, Bandung City, the types are: Aspergillus fumigatus, Aspergillus niger and Aspergillus terreus.